2004
DOI: 10.1783/0000000042177063
|View full text |Cite
|
Sign up to set email alerts
|

Unanswered questions in contraceptive management: What do the experts do?

Abstract: Context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Because of reduced fertility and a diminishing need for a powerful contraceptive in premenopausal women, and because synthetic estrogens in the COC are prothrombotic even in healthy women, a generally accepted policy is to switch to an alternative method no later than 50 or 51 years of age 9,[40][41][42] . For women up to that age, who may have difficulty in remembering to take the COC daily, the transdermal combined contraceptive patch designed to deliver norelgestromin and ethinylestradiol, and the combined contraceptive vaginal ring releasing etonogestrel and ethinylestradiol offer new hope.…”
Section: Hormonal Methods Combined Oral Contraceptivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of reduced fertility and a diminishing need for a powerful contraceptive in premenopausal women, and because synthetic estrogens in the COC are prothrombotic even in healthy women, a generally accepted policy is to switch to an alternative method no later than 50 or 51 years of age 9,[40][41][42] . For women up to that age, who may have difficulty in remembering to take the COC daily, the transdermal combined contraceptive patch designed to deliver norelgestromin and ethinylestradiol, and the combined contraceptive vaginal ring releasing etonogestrel and ethinylestradiol offer new hope.…”
Section: Hormonal Methods Combined Oral Contraceptivesmentioning
confidence: 99%
“…Although the progestogen-only pill (POP) has been available for several years, it has limited acceptability and accounts for less than 10% of the current oral contraceptive market in the UK 41,48 . The POP is currently used by 7% of women aged over 40 years 39 .…”
Section: The Progestogen-only Pillmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the licensing and the advice from pharmaceutical companies was conservative and, in many scenarios, a majority of practitioners indicated that in order to serve the best interests of their clients they felt constrained to practise outside the Summary of Product Characteristics (Brooker and Guillebaud 2004).…”
Section: Practice Habitsmentioning
confidence: 99%